FORMULATION AND EVALUATION OF METRONIDAZOLE TABLETED MICROSPHERES FOR COLON DRUG DELIVERY - Singh, Shivangi; C, Nithya Shanthi; K Mahato, Arun (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The need of this study was to develop tableted microspheres that can be targeted to colon because metronidazole (MNZ) has good solubility at pH 1.2; hence, coating of the drug with the suitable pH dependent is done to prevent its release in the gastric region. Methods: Colon targeted tablets of MNZ were prepared with enteric coated microspheres using pH dependent polymers such as cellulose acetate phthalate, hydroxypropyl methylcellulose phthalate, and Eudragit S 100 by solvent evaporation method. All the formulations were prepared by changing drug-polymer ratio from 1:1 to 1:5 and the interactions of the drug with polymers were studied by Fourier transform infrared and thermal analysis. Results: Formulations F 5 , F 8 , and F were found to best optimized in percentage yield, drug entrapment efficiency, mean particle size and in vitro drug release. The result obtained were found in the desired ranges where % yield ranging from 52.56% to 98.253%, drug entrapment efficiency from 42.17% to 99.017%, and mean particle size from 36.774 to 229.961 Âµm. Then, tablet of optimized formulations was prepared by direct compression method and in vitro drug release was performed. All the parameters of tablets were found acceptable as per IP guideline. Around 4-10% drug release was in 0.1 N HCl after 2 hrs, 50% release at pH 7.4 phosphate buffer within 5 hrs, maximum retardation was found in the formulation of Eudragit S 100. Scanning electron microscopy permitted a surface topographical analysis. 14 Conclusion: The MNZ tableted microspheres showed their release at pH 7.4 thus this experimental work can be used to improve absorption of drug in colon for successful treatment of the disease. Keywords: Metronidazole, Tableted microspheres, Solvent evaporation method, Direct compression method.